Th17 cells: interactions with predisposing factors in the immunopathogenesis of inflammatory bowel disease. (February 2012) - Raza, Ali; Yousaf, Wajeeha; Giannella, Ralph; Shata, Mohamed Tarek
Inflammatory bowel disease (IBD) is a chronic inflammatory state of the GI tract of unknown etiology. Classically, tissue injury in IBD is thought to be primarily mediated by Th1 cells in Crohn''s disease or Th2 cells in ulcerative colitis. The discoveries of new subsets of T-helper cells, especially Th17 cells, have revolutionized our understanding of the disease immunopathology. Th17 cells seem to affect both innate and adaptive immune responses by the release of regulatory cytokines. Understanding the role of Th17 cells in IBD pathogenesis and targeting their regulatory cytokines may provide potential therapeutic approaches for the treatment of IBD in the future.